Comparative study of concrete wastes as low-cost adsorbent for copper removal from aqueous solution - Nur Syahirah Mohd Noor,; Budhi Primasari,; Warid Wazien Ahmad Zailan,; Zadariana Jamil, (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
The presence of copper in water sources poses significant environmental and health risks, requiring effective removal strategies. Adsorption is one of the most efficient processes to treat contaminated water due to its advantages such as availability, low cost, and eco-friendly nature. This study explores the potential of utilizing concrete wastes as a low-cost adsorbent for the copper ions removal from aqueous solutions. Two types of concrete wastes have been used as low-cost adsorbents in this study: i) normal concrete waste (NCW) with mix proportion of Cement, water, aggregates 20, aggregates 10, sand and ii) modified concrete waste (MCW) with Cement, water, aggregate 10, sand, superplasticizer (2% cement), silica fume (10% cement). The uptakes of copper ions on NCW and MCW were studied at different initial metal Cu2+ ion concentrations, pH, adsorbent dosages and contact time. The maximum removal efficiency of copper removal for both types of concrete wastes achieved 99.99% at pH 5.0 for both NCW and MCW at equilibrium conditions. The maximum metal uptakes capacity achieved at 0.6 mg/g for both NCW and MCW exhibits good adsorption characteristics. The NCW adsorption data fitted well with Langmuir isotherm (R2= 1), whilst the MCW data obeyed Freundlich isotherm (R2 = 0.9889)